2019
DOI: 10.4236/wja.2019.93011
|View full text |Cite
|
Sign up to set email alerts
|

Kinases: Understanding Their Role in HIV Infection

Abstract: Antiviral drugs currently on the market primarily target proteins encoded by specific viruses. The drawback of these drugs is that they lack antiviral mechanisms that account for resistance or viral mutation. Thus, there is a pressing need for researchers to explore and investigate new therapeutic agents with other antiviral strategies. Viruses such as the human immunodeficiency virus (HIV) alter canonical signaling pathways to create a favorable biochemical environment for infectivity. We used Qiagen Ingenuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Also, calcium/calmodulin-dependent protein kinase 1D (CAMK1D) was downregulated by HIV-1. The activity of CAMK1D was found to be negatively regulated by HIV-1 infection, which was in correlation with our results, wherein we observed decreased mRNA levels [ 37 ]. It was also shown that siRNA knockdown of CAMK1D can inhibit HIV-1 infection [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, calcium/calmodulin-dependent protein kinase 1D (CAMK1D) was downregulated by HIV-1. The activity of CAMK1D was found to be negatively regulated by HIV-1 infection, which was in correlation with our results, wherein we observed decreased mRNA levels [ 37 ]. It was also shown that siRNA knockdown of CAMK1D can inhibit HIV-1 infection [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among the potential signaling pathways often targeted by retroviruses, ERVK IN-associated cascades emerged as Forkhead box O (FoxO) signaling [ 75 ], p53 signaling [ 76 ], ErbB signaling [ 77 ], Wnt signaling [ 78 ], modulation of kinase activity [ 79 , 80 ], and multiple aspects of immune signaling [ 81 ] ( Figure 4 ). Within these pathways, prominent immune-related signaling intermediates included STAT3 [ 55 ], STAT5 [ 56 ], and TRAF2 [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous report identified Sik1 in an ingenuity pathway analysis of kinases regulating HIV-1, however, it was not studied further [21]. Our experimental study illustrates that SIK inhibitors perturb the cellular circadian clock, reduce rhythmic HIV-1 replication and inhibit viral replication in primary T Pharmacological and genetic disruption of SIKs reduced TNFα mediated reactivation of HIV-1 in the J-Lat T cell model, altogether highlighting a pro-viral role for SIKs in regulating HIV-1 infection.…”
Section: Resultsmentioning
confidence: 98%
“…A previous report identified Sik1 in an ingenuity pathway analysis of kinases regulating HIV-1, however, it was not studied further [ 21 ]. Our experimental study illustrates that SIK inhibitors perturb the cellular circadian clock, reduce rhythmic HIV-1 replication and inhibit viral replication in primary T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation